Policy and Governance Towards Eliminating of Malaria Among Children Under Five in Four Districts of Ghana - Amoako, Martha; Verter, Nahanga (European Journal of Sustainable Development, 2022)
Malaria contributes significantly to the increasing mortality rate among Ghana's children under-five years of age (U5). This study sought to analyze how policies, actors, and institutions play out and interact in Ghana´s public health sector and how they affect the health outcomes of children U5 in early childhood malaria in four districts. The study findings show current health policies to tackle malaria among children U5. However, there were apparent discrepancies between policy intent and actual implementation, just as other key stakeholders are not adequately involved in policy formulations and executions in the districts. The study concludes that a functioning health system governance is critical to achieving desired results in eradicating malaria among children U5 in the four communities understudied. Keywords: children U5, governance, healthcare, health policy, malaria